Pengaruh Viral Marketing dan Brand Ambassador Boyband SEVENTEEN Terhadap Minat Beli Susu UHT Indomilk di Kota Jakarta Pusat. - Salsabilla, Nurahma Amelia; Mariyono, Joko; Handayani, Migie (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the influence of viral marketing, the use of boyband SEVENTEEN as a brand ambassador, and consumer characteristics such as age, gender, and education level on the purchase intention of Indomilk UHT milk products in Central Jakarta. The research was conducted online from November to December 2024, with respondents residing in Central Jakarta through social media platforms. The research method employed is a survey method. The sampling technique used is purposive sampling with a sample size of 100 respondents based on specific criteria. The data analysis method used is descriptive quantitative analysis with multiple linear regression analysis. The results indicate that the respondent characteristics are predominantly from the age group of 17-24 years, female consumers, and those with a high school education. The findings show that the main variables (Viral Marketing and Brand Ambassador) and control variables (Age, Gender, and Education Level) have both simultaneous and partial effects on the purchase intention of Indomilk UHT milk in Central Jakarta